A Knowledge Management-extended Gamified Customer Relationship Management System - Lee, Chien Sing *; Foo, Jun Jie *; Vinudha, Jeya Sangar *; Chan, Pei Yee *; Hor, Weng Keen *; Chan, Eng Keong * (2017)
The growth of Smart Cities often depends on global trends, human capital, foreign investments and partnerships, as well as citizen participation. With these drivers in mind, we focus on the question of how to attract and maintain customers first through a Gamified Customer Relationship Management System and subsequently, its enhancement via a Knowledge Management approach. The design of the gamified customer relationship management system and subsequently, its extension via a Knowledge Management approach are presented along with simple text mining on data from the Website’s forum. Findings towards user acceptance and user satisfaction are positive and directly lends towards possible Big Data and possibly, IoT applications in the future.